A Rational Design of Highly Controlled Suzuki-Miyaura Catalyst-Transfer Polycondensation for Precision Synthesis of Polythiophenes and Their Block Copolymers: Marriage of Palladacycle Precatalysts with MIDA-Boronates - Seo, Kyeong Bae; Lee, In Hwan; Lee, Jaeho; Choi, Inho; Choi, Tae Lim (Journal of the American Chemical Society, 2018)
Herein, we report a highly efficient Suzuki-Miyaura catalyst-transfer polycondensation (SCTP) of 3-alkylthiophenes using bench-stable but highly active Buchwald dialkylbiarylphospine Pd G3 precatalysts and N-methylimidodiacetic (MIDA)-boronate monomers. Initially, the feasibility of the catalyst-transfer process was examined by screening various dialkylbiarylphospine-Pd(0) species. After optimizing a small molecule model reaction, we identified both RuPhos and SPhos Pd G3 precatalysts as excellent catalyst systems for this purpose. On the basis of these model studies, SCTP was tested using either RuPhos or SPhos Pd G3 precatalyst, and 5-bromo-4-n-hexylthien-2-yl-pinacol-boronate. Poly(3-hexylthiophene) (P3HT) was produced with controlled molecular weight and narrow dispersity for a low degree of polymerization (DP) only, while attempts to synthesize P3HT having a higher DP with good control were unsuccessful. To improve the control, slowly hydrolyzed 5-bromo-4-n-hexylthien-2-yl-MIDA-boronate was introduced as a new monomer. As a result, P3HT and P3EHT (up to 17.6 kg/mol) were prepared with excellent control, narrow dispersity, and excellent yield (>90%). Detailed mechanistic investigation using 31P NMR and MALDI-TOF spectroscopy revealed that both fast initiation using Buchwald precatalysts and the suppression of protodeboronation due to the protected MIDA-boronate were crucial to achieve successful living polymerization of P3HT. In addition, a block copolymer of P3HT-b-P3EHT was prepared via SCTP by sequential addition of each MIDA-boronate monomer. Furthermore, the same block copolymer was synthesized by one-shot copolymerization for the first time by using fast propagating pinacol-boronate and slow propagating MIDA-boronate.
Keywords: Catalyst system; Catalyst transfers; Controlled molecular weight; Maldi-tof spectroscopies; Narrow dispersity; Poly-3-hexylthiophene; Rational design; Sequential addition